Large mode area multi segmented-trench crisscross fiber with resonance and leakage. (August 2022) - Ma, Shaoshuo; Sun, Danyang; Jiang, Xiaohui; Cheng, Wenjing; Liang, Guo; Wen, Yuan
Highlights: A novel multi segmented-trench crisscross fiber (STCF) is proposed. The multi STCF has excellent HOMs suppression and larger mode area property. A large mode area of 987 μm 2 is achieved with HOMs suppression larger than 100. The fiber can hold single mode operation under certain heat load. Abstract: In this paper, a multi segmented-trench crisscross fiber (STCF) is proposed. The multi STCF is designed from the segmented cladding fiber (SCF) and multi-trench fiber (MTF). A multi STCF is a SCF whose low index claddings are cut off by two layers of high index rings, then rotate the middle layer claddings. The high index rings are inserted into claddings to add the effect of resonance. The rotation of middle layer claddings makes the claddings distribution crisscross, thus restricting the excessive loss of core modes. Multi STCF is researched and compared to others four fibers with similar structures. The multi STCF has great advantages on large mode area and single-mode operation. When the bending radius is 20 cm, the multi STCF core radius can extend to 27 μm. And the mode area achieves 987 μm 2 while simultaneously keeping large high order modes suppression. Multi STCF combines the resonance and leakage effects to adjust mode loss while enlarging the mode area. Besides, the fiber can also suit single-mode operation under certain heat load. This research has meaningful values on high power fiber lasers.